PENGENALAN METODE INQUIRI DALAM PEMBELAJARAN IPA DI SDN 6 UBUNG DENPASAR - Wendri, Nyoman; Susilawati, Made (Prosiding Seminar Nasional MIPA, 2013)
Abstract Â  Technological developments will not be separated from the development in the field of Natural Sciences (IPA). Development of the field of science is not likely to occur if not accompanied by an increase in the quality of science education, has been teaching science while considered a difficult subject. Inquiri is a learning process based on the search and discovery through systematic thinking process. This activity is done in SDN 6 Ubung Denpasar on fourth grade students. This activity aims to increase the understanding of materials science in the fourth grade students of SDN 6 Ubung Denpasar and increase student interaction in the classroom in the following learning science. IPA materials covered are the parts of the plant. Analysis results obtained mean = 71.79 which indicates that the average student evaluation results for the discussion of the parts of the plants is 71.79, this value is greater than the average value of the specified class, which is 65. T-test results also showed t = 4.40 with p = 0.000 smaller 0.05. This means learning implemented effectively enhance students' understanding and knowledge of the science subjects